SPIRITUAL REFORMS IN THE NEW UZBEKISTAN AS A FACTOR OF SOCIAL DEVELOPMENT (Scientific journal of the Fergana State University, 2026)
In this article, spiritual potential is the development of forms of social consciousness of the society, raising the worldview and spiritual world of its members, preserving the centuries-old spiritual heritage and passing it on to future generations, ensuring spiritual security. It is explained that it is a set of possibilities and tools that can be used in this regard.